Status Kewarisan Anak di Luar Nikah: Telaah atas Pemikiran Syi'ah Imamiyyah - Irma Rumtianing U.H (Justicia Islamica, 2009)
This study aims to examine the inheritance status of children born out of wedlock from the perspective of Imamiyyah Shi'ite thought. Using a qualitative method and a normative-theological approach, this study examines Shi'ite fiqh literature and compares it with the views of the Sunni school. The results show that the Imami Shi'ites provide greater opportunities for children born out of wedlock to obtain certain rights, including inheritance from the mother, but not from the father, unless there is recognition. This approach is based on the principle of justice and protection of the rights of children as individuals. This study shows significant differences in the interpretation of inheritance law between Islamic schools of thought, as well as the importance of a contextual approach in addressing modern family issues.